Two Rural Worlds: Differences of Rural High School Students' Motivational Profiles in Indiana and Colorado - Patricia L. Hardre; Maeghan N. Hennessey (Journal of Research in Rural Education, 2010)
This research examined how rural high school students' self-perceptions and environmental perceptions influence their engagement, expectations, and achievement, and how those relationships differ by geographic rural location. Participants were 224 students in four rural, public high schools in two U.S. states, Colorado and Indiana. Path models followed by multivariate regression analyses, and MANOVAs were utilized to examine relationships among variables and test for group differences. Overall, a single, generic motivational model did not fit well for the two-state rural sample. At the state level, the two subsamples demonstrated unique significant paths, some shared and others divergent. School differences (within states) were largely non-significant, supporting the case for unique profiles attributable to state-level influences on rural contexts. Both demonstrated theoretically-consistent relationships, but with different strengths in the paths. Colorado's motivational profile is more complex, while Indiana's is more straightforward, with fewer significant paths and mediating relationships. By subject area, math was motivationally higher than other subjects. These findings present potentially important implications for rural schools in resource management, administration and teaching practice.